A Classroom Action Research: Empowering Students English Grammar Proficiency through PPP (Presentation, Practice, Production) Strategy - Raj Kaur, Bal Janatte; Desty Febria; Maya Marsevani (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2025)
This study investigates the impact of the Presentation, Practice, and Production (PPP) strategy on enhancing English grammar proficiency among high school students in Batam City. Grammar is essential for effective communication, yet students often struggle due to its complexity, differences from their native languages, and fear of ridicule. Utilizing Classroom Action Research (CAR) over three months with 45 students, the study employed a cyclical process of planning, action, observation, and reflection. Pre-test and post-test evaluations revealed a significant improvement in grammar skills, with average scores rising from 70.00 to 82.62. The PPP method effectively addresses grammar learning challenges by introducing concepts (Presentation), facilitating controlled practice (Practice), and encouraging creative use in communication (Production). The implications of these findings underscore the importance of tailored instructional methods that foster a supportive environment, reducing anxiety and building students' confidence. Integrating the PPP strategy into curriculum development can enhance language learning across diverse contexts, promoting greater student engagement and improved outcomes. Ultimately, this study aims to empower students in their language learning journey, ensuring that all learners, regardless of initial proficiency, can achieve desired outcomes in English communication skills.